Kinetics and muscular function in alpine skiing - Müller, E.; Kroell, J.; Schiefermüller, C.; Wakeling, J. M. (Neuromuscular aspects of sport performance, 2011)
This chapter contains sections titled: Introduction, The Dynamics of downhill skiing, Biomechanics of carving techniques, Muscle functions and muscle fatigue in recreational skiing, References.